SuperGAG biopolymers for treatment of excessive bladder permeability - Rheal A. Towner; Beverley Greenwood‐Van Meerveld; Ehsan Mohammadi; Debra Saunders; Nataliya Smith; Grannum R. Sant; Harrison C. Shain; Thomas H. Jozefiak; Robert E. Hurst (Wiley, 2021)
Abstract Few therapeutic options exist for treatment of IC/BPS. A novel high MW GAG biopolymer ("SuperGAG") was synthesized by controlled oligomerization of CS, purified by TFF and characterized by SEC‐MALLS and 1H‐NMR spectroscopy. The modified GAG biopolymer was tested in an OVX female rat model in which bladder permeability was induced by a 10‐minute intravesicular treatment with dilute (1 mg/ml) protamine sulfate and measured by classical Ussing Chamber TEER measurements following treatment with SuperGAG, chondroitin sulfate, or saline. The effect on abrogating the abdominal pain response was assessed using von Frey filaments. The SuperGAG biopolymer was then investigated in a second, genetically modified mouse model (URO‐MCP1) that increasingly is accepted as a model for IC/BPS. Permeability was induced with a brief exposure to a sub‐noxious dose of LPS and was quantified using contrast‐enhanced MRI (CE‐MRI). The SuperGAG biopolymer restored impermeability to normal levels in the OVX rat model as measured by TEER in the Ussing chamber and reduced the abdominal pain response arising from induced permeability. Evaluation in the URO‐MCP1 mouse model also showed restoration of bladder impermeability and showed the utility of CE‐MRI imaging for evaluating the efficacy of agents to restore bladder impermeability. We conclude novel high MW SuperGAG biopolymers are effective in restoring urothelial impermeability and reducing pain produced by loss of the GAG layer on the urothelium. SuperGAG biopolymers could offer a novel and effective new therapy for IC/BPS, particularly if combined with MRI to assess the efficacy of the therapy.